Intégrer la connectivité paysagère dans la séquence ERC : une approche par la quantité d'habitat atteignable - Laurent Bergès; Catherine Avon; Lucie Bezombes; Céline Clauzel; Rémi Duflot; Jean-Christophe Foltête; Stéphanie Gaucherand; Xavier Girardet; Thomas Spiegelberger (VertigO)
National, European and international commitments have been made to maintain and restore the connectivity of natural habitats to face habitat loss and fragmentation. Meanwhile, environmental policies in different countries worldwide have proposed the mitigation hierarchy to reach the goal of "no net loss (NNL) of biodiversity". The mitigation hierarchy aims at assessing all the ecological impacts of a development project, but the impacts on landscape connectivity are not properly addressed. We propose an operational framework to assess the environmental impacts of a development project on landscape habitat connectivity. This framework is based on graph theory and the equivalent connectivity index EC of "amount of reachable habitat", which takes into account the total amount of habitat, the spatial configuration of habitat patches and the dispersal capacities of the species. We redefine the three main issues of the mitigation hierarchy regarding "no net loss of connectivity". Then, this framework was applied to a simple, virtual network case where several scenarios of impact avoidance, reduction and compensation were tested and compared. We discuss the benefits and limitations of this approach for the mitigation hierarchy and provide practical recommendations for implementation. In conclusion, we advocate and justify a better integration of the three main biodiversity conservation policies in France : the law for the recovery of biodiversity, nature and landscapes, the SRADDET and the strategy for the establishment of protected areas.